Images of Asteroid 21 Lutetia: A Remnant Planetesimal from the Early Solar System - Sierks, H.; Lamy, P.; Koschny, D.; Rickman, H.; Rodrigo, R.; A'Hearn, M. F.; Angrilli, F.; Barucci, M. A.; Bertaux, J. L.; Besse, S.; Carry, B.; Cremonese, G.; et al. (Science, 2011)
Images obtained by the Optical, Spectroscopic, and Infrared Remote Imaging System (OSIRIS) cameras onboard the Rosetta spacecraft reveal that asteroid 21 Lutetia has a complex geology and one of the highest asteroid densities measured so far, 3.4 ± 0.3 grams per cubic centimeter. The north pole region is covered by a thick layer of regolith, which is seen to flow in major landslides associated with albedo variation. Its geologically complex surface, ancient surface age, and high density suggest that Lutetia is most likely a primordial planetesimal. This contrasts with smaller asteroids visited by previous spacecraft, which are probably shattered bodies, fragments of larger parents, or reaccumulated rubble piles.